Pengaruh Lingkungan Kerja Nonfisik, Reward, Punishment Terhadap Produktivitas Kerja Pegawai Dinas Penanaman Modal Dan PTSP Jombang - Della Nur Aulya; Udik Jatmiko; Dadang Afrianto (Universitas 17 Agustus 1945 Semarang, 2023)
The purpose of this study was to determine the effect of non-physical work environment, reward and punishment on the work productivity of employees of the Jombang Investment and PTSP Office. This study uses a quantitative approach, with a sample size of 35 respondents. The sampling method uses saturated sampling. Data collection was done through distributing questionnaires. Data analysis techniques in this study used validity test, reliability test, normality test, linearity test, heteroscedasticity test, multicollinearity test, multiple linear regression analysis, t test, F test, and coefficient of determination (R^2). The results showed that the non-physical work environment, reward and punishment partially had a significant effect on work productivity and the non-physical work environment, reward and punishment simultaneously had a significant effect on work productivity.